Antibacterial Activity and Chemical Composition of Red Peacock Flower (Caesalpinia pulcherrima L.) Leaf Essential Oil - Novena Risnalani Rintank Constani; Hartati Soetjipto; Sri Hartini (Jurnal Kimia Sains dan Aplikasi, 2019)
Peacock flower (Caesalpinia pulcherrima L.) leaves contain essential oils which can be used as an ingredient in cosmetics, perfume, aromatherapy, medicine, and supplements. The study was conducted to obtain essential oils from peacock flower leaves and determine the antibacterial activity against gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and gram-negative (Escherichia coli and Pseudomonas aeruginosa). Antibacterial activity test was carried out by the agar diffusion method, using paper discs. Measurements were made for the inhibition zone diameter (IZD) that appeared, while the essential oil component was analyzed using GC-MS. The results showed that the peacock flower leaves (C. pulcherrima) had a moderate to strong antibacterial effect at a concentration of 7.5%-20% against gram-positive bacteria (B. subtilis and S. aureus) and gram-negative bacteria (E. coli and P. aeruginosa). Gram-negative E. coli bacteria are relatively more sensitive to peacock flower leaf essential oil compared to other test bacteria. Peacock flower (C. pulcherrima) leaf essential oil is composed of 7 main components namely β-Cubebene 33.87%; Caryophyllene 23.00%; γ-Elemene 13.18%; α-Pinene 10.96%; Cadina-1(10),4-diene 10.20%; Copaene; 7.09%; β-Pinene 1.70%.